Pembelajaran Google Classroom dan Metode Belajar PAI Berbasis E-Learning - Ade Jamarudin; Anwar Sanusi; Yundri Akhyar; Ofa Ch Pudin (Institute of Computer Science (IOCS), 2022)
PAI is one of the compulsory subjects in schools, starting from the elementary level to the secondary level, playing an important role in achieving national education goals as mandated in Law no. 20 of 2003 concerning the National Education System. In the implementation of PAI learning, of course, it requires learning media. Google Classroom is an online platform that makes it easy for teachers in the digital learning process with students, teachers can create classes in program, give students additional codes or invite via email, and start communicating about class information, assignments, and documents. The research method used in this research is descriptive analytic. Analytical descriptive method is a to provide an overview of situations and accumulate data, as well as provide an explanation and analysis of the data obtained from the research site. This program makes it easy for PAI teachers and students if they cannot meet face to face in real classes. PAI teachers no longer need to go to school to give an assignment to the school picket section, because with the presence of this application, PAI teachers can share assignments and communicate with students remotely that they cannot enter and are given assignments, even in terms of time collection. determined immediately.